The Impact of Social Media on the Decline of Formal Writing: A Comparative Study of Digital and Traditional Discourse - Jeryo, Raqib Abbas; Hamzah, Murtadha Hamid; Kamal, Rusul Neima; AL Shujairi, Fatimah AbdulJaleel; Muhi, Halla Haider; Saadoon, Rasha Ihsan; Hamad, Baraa Sattar (Manar Elsharq Journal for Literature and Language Studies, 2025)
This study investigates the influence of digital social media Iraqi EFL students’ formal writing skills in Baghdad. This study aimed to ascertain the extent to which digital social media affect the formal writing skills of Iraqi EFL students, explore the perspectives, and lived experiences of both EFL learners and their educators regarding the relationship between social media usage and the cultivation of formal writing competence. The research employed a qualitative case study design. Interviewing both lecturers and engaging students in focus groups. Findings indicate a decline in adherence to formal writing conventions, alongside potential enhancement of speaking skills. This research firmly establishes the necessity for explicit instruction in register variation and responsible digital communication within EFL education.